Dye Degradation using Saccharomyces Cerevisiae - Mathivanan, Mahalakshmi; V, Prabinth; Chinnaiah S, Selvin; Sundaram RS, Shanmuga (International Journal of Engineering and Technology, 2018)
Disposal of dyes into the environment causes serious damage and they may be toxic to some aquatic organisms due to their breakdown products. The colouring pigments present in the effluent may give aesthetic look and it affects the photosynthetic in plants.Â  The chemical and physical methods have many disadvantages which can overcome by biological method because it is cost saving and environmentally benign. In biological methods, absorbents like Bacteria, fungus, cellular membrane etc. can be used. Since yeast is cheap and more effective it is preferred. In the present study an attempt was made to examine the potential of Saccharomyces Cerevisiae in decolorization of Congo red dye. The influence of different condition in variation of concentration, time and pH in that Study was made to find the optimum condition in which the maximum decolorization was occur. The UV Spectrum shows the maximum wavelength was observed in 496.93. At room temperature, the maximum decolorization of 90.7% was observed in the concentration of 40 ppm(0.004g/100ml) and it took place after 18hrs. In the next experiment, maximum decolorization of 96.88% was obtained in the concentration of 40ppm(0.004g/100ml) and pH of 4 at a time of 17hrs with a dosage of 0.1g in room temperature which is considering to be the optimum condition. The above results show the potential of this Saccharomyces Cerevisiae to be used in the biological treatment of textile effluent under optimum condition.Â Â